2020
DOI: 10.1186/s12885-020-07168-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the results and hematological side effects of 3D conformal and IMRT/ARC therapies delivered during craniospinal irradiation of childhood tumors with a follow-up period of five years

Abstract: Background Craniospinal irradiation (CSI) of childhood tumors with the RapidArc technique is a new method of treatment. Our objective was to compare the acute hematological toxicity pattern during 3D conformal radiotherapy with the application of the novel technique. Methods Data from patients treated between 2007 and 2014 were collected, and seven patients were identified in both treatment groups. After establishing a general linear model, acute blood toxicity results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…IMRT and VMAT allow for a more conformal dose distribution to the PTV and lower doses to adjacent organs at risk; however, treatment planning requires more time and more normal tissue will receive lower doses of radiation [20, 21]. Retrospective studies have found less hearing loss after IMRT/VMAT compared to conventional or 3D conformal radiotherapy [22], while other side effects, such as hematologic toxicity or neurocognitive decline, do not appear significantly different between IMRT/VMAT and 3D conformal radiotherapy [23, 24].…”
Section: Modalities Of Radiation Treatmentmentioning
confidence: 99%
“…IMRT and VMAT allow for a more conformal dose distribution to the PTV and lower doses to adjacent organs at risk; however, treatment planning requires more time and more normal tissue will receive lower doses of radiation [20, 21]. Retrospective studies have found less hearing loss after IMRT/VMAT compared to conventional or 3D conformal radiotherapy [22], while other side effects, such as hematologic toxicity or neurocognitive decline, do not appear significantly different between IMRT/VMAT and 3D conformal radiotherapy [23, 24].…”
Section: Modalities Of Radiation Treatmentmentioning
confidence: 99%